2017
DOI: 10.3389/fphar.2017.00256
|View full text |Cite
|
Sign up to set email alerts
|

SRT1720 Alleviates ANIT-Induced Cholestasis in a Mouse Model

Abstract: Intrahepatic cholestasis is a kind of clinical syndrome along with hepatotoxicity which caused by intrahepatic and systemic accumulations of bile acid. There are several crucial generating factors of the pathogenesis of cholestasis, such as inflammation, dysregulation of bile acid transporters and oxidative stress. SIRT1 is regarded as a class III histone deacetylase (HDAC). According to a set of researches, SIRT1 is one of the most important factors which can regulate the hepatic bile acid metabolism. SRT1720… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 46 publications
3
20
0
Order By: Relevance
“…2E). Celastrol, a pentacyclic triterpene found in the roots of the Tripterygium Wilfordi (thunder god vine), was able to increase Sirt1 mRNA levels (25). In agreement with a previous study, Sirt1 mRNA levels and SIRT1 protein levels were significantly induced and Ac-p53 levels were significantly decreased by 0.1 and 1.0 M celastrol in primary mouse hepatocytes (Fig.…”
Section: Molecular and Cellular Proteomics 183 523supporting
confidence: 91%
“…2E). Celastrol, a pentacyclic triterpene found in the roots of the Tripterygium Wilfordi (thunder god vine), was able to increase Sirt1 mRNA levels (25). In agreement with a previous study, Sirt1 mRNA levels and SIRT1 protein levels were significantly induced and Ac-p53 levels were significantly decreased by 0.1 and 1.0 M celastrol in primary mouse hepatocytes (Fig.…”
Section: Molecular and Cellular Proteomics 183 523supporting
confidence: 91%
“…The release of reactive oxygen and nitrogen species and the associated nitro-oxidative stress play a key role in the pathogenesis of different types of liver injury including cholestatic damage [5,23]. In the current study, elevations of lipid peroxidation and reduced antioxidant statuses were observed among the hepatic tissues of LCA-treated animals.…”
Section: Discussionmentioning
confidence: 68%
“…Nrf2 can regulate the expression and activation of variety of enzymes that counteract oxidative stress and promote cell survival [30,31]. In addition, studies have shown that the activation of Nrf2 can safeguard against cholestasis caused by bile duct ligation and alphanaphthyl isocyanate models via the induction of many anti-oxidative genes [5,32,33]. The induction of HO-1 can confer hepatoprotection in various models of hepatic injuries [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations